Super-high-resolution aerial imagery, digital surface model and 3D point cloud of Ketik Fire Scar, Alaska (subset 04) - Rettelbach, Tabea; Nitze, Ingmar; Grünberg, Inge; Hammar, Jennika; Schäffler, Simon; Hein, Daniel; Gessner, Matthias; Bucher, Tilman; Brauchle, Jörg; Hartmann, Jörg; Sachs, Torsten; Boike, Julia; et al. (In: Rettelbach, T et al. (2024): Super-high-resolution aerial imagery, digital surface models and 3D point clouds of the Ketik Fire Scar, Alaska [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.962272, 2024)
As part of the ThawTrend-Air airborne campaign led by the Alfred Wegener Institute in 2019, we collected super-high-resolution multispectral imagery of permafrost landscapes with the Modular Aerial Camera System (MACS), developed by the German Aerospace Center. From these images, we photogrammetrically processed four-band orthophotos (blue, green, red, near-infrared) and digital surface models at a spatial resolution of 7 cm, as well as photogrammetric point clouds in RGB and NIR at 35.13 pts/m² and 11.51 pts/m², respectively. This dataset covers approximately 9.60 km² of the Ketik fire scar in Alaska, with all images collected on 27 July 2019. This super-high-resolution dataset provides opportunities for generating detailed training datasets of permafrost landform inventories, a baseline for change detection for thermokarst and thermo-erosion processes, and upscaling of field measurements to lower-resolution satellite observations.
Keywords: Airborne Data; Alaska; Arctic Landscape Dynamics; Digital Surface Model; Fire Scar; Ice-wedge Polygons; MACS; Orthoimagery; Permafrost; point clouds; Structure-from-Motion